Antioxidant Activity and Total Flavonoid of Carica papaya L. Leaves with Different Varieties, Maturity and Solvent - Fatma Zuhrotun Nisa; Mary Astuti; Sofia Mubarika Haryana; Agnes Murdiati (agriTECH, 2019)
Carica papaya leaves are one of the vegetables consumed by Indonesian people, especially in Java Island. Carica papaya is easy to grow in Indonesia and has many variants, so, Carica Papaya leaves is a local potent to be developed for functional food and nutraceutical. The aim of this study was to investigate antioxidant activity and total flavonoids of Carica papaya leaves with different varieties, maturity and solvent. Carica papaya leaves (CPL) was firstly extracted by methanol to select two CPLs with high antioxidant capacity and total flavonoid. The two selected CPLs were further tested with different ages mainly young and mature leaves. One selected CPL was further tested with different extraction solvents. Antioxidant activity was determined by 2.2 diphenyl-1-picrylhydrazyl, DPPH and Ferric reducing antioxidant power, FRAP. This study used five varieties of Carica papaya leaves, namely Bangkok, California, Purple, Golden and Grendel. The result showed that Golden and Grendel varieties had a higher percentage of radical scavenging property than the others, which was 78.37% and 77.40% by the DPPH method. Grendel and Purple had a higher percentage of radical scavenging property, which was 45.82 and 34.32 mmol/mg. Grendel and Purple had a higher total flavonoid property, which was 50.33 and 46.02 µg/g. Mature leaves had a higher percentage of radical scavenging property than young leaves by DPPH and FRAP methods. Mature leaves had a higher total flavonoid property than young leaves in both Grendel and Purple. Grendel had a higher antioxidant activity and a higher total flavonoid property than Purple. Grendel with water extraction had a higher antioxidant activity by DPPH and FRAP methods. The total flavonoid of Grendel papaya leaves’ extract with water extraction was lower than ethanol 70% and methanol.